OCCURRENCE OF MYCORRHIZAE IN SOME SPECIES OF CAREX (CYPERACEAE) OF THE DARJEELING HIMALAYAS, INDIA: Life Science-Botany - GHOSH, ASOK; BHUJEL, SHEKHAR; GOPAL MAITI, GAUR (International Journal of Life Science and Pharma Research, 2014)
The Cyperaceae (sedge family) have generally been considered non-mycorrhizal, although recent evidences suggest that mycotrophy may be considerably more widespread among sedges than was previously realized. In this study, 28 in situ populations of 12 species of Carex L.(C. myosurus Nees, C. composita Boott, C. cruciata Wahl., C. filicina Nees, C. inanis Kunth, C. setigera D. Don, C. insignis Boott, C. finitima var. finitima; C. fusiformis Nees subsp. finitima (Boott) Noltie, C. teres Boott, C. longipes D. Don ex Tilloch and Taylor, C. nubigena D. Don ex Tilloch and Taylor and C. rochebrunii subsp. rochebrunii; C. remota Linnaeus subsp. rochebrunii (Franchet and Savatier) Kükenthal) occurring in the Darjeeling Himalayas were surveyed. Mycorrhizal infection by VAM (Vesicular Arbuscular Mycorrhiza) fungi was found in roots of 9 species (C. myosurus, C. composita, C. cruciata, C. filicina, C. inanis, C. setigera, C. finitima, C. teres, and C. nubigena) and appears to occur in response to many factors, both environmental and phylogenetic. In non-mycorrhizal species, a novel root character, the presence of bulbous-based root hairs, was identified.